Comprehensive Analysis of a Ferroptosis Pattern and Associated Prognostic Signature in Acute Myeloid Leukemia - Cui, Zelong; Fu, Yue; Yang, Zongcheng; Gao, Zhenxing; Feng, Huimin; Zhou, Minran; Zhang, Lu; Chen, Chunyan (Frontiers in Pharmacology, 2022)
Ferroptosis is a widespread form of programmed cell death. The environment of cancer cells makes them vulnerable to ferroptosis, including AML cells. Yet the specific association between ferroptosis and AML outcome is little known. In this study, we utilized ferroptosis related genes to distinguish two subtypes in a TCGA cohort, which were subsequently validated in independent AML cohorts. The subtypes were linked with tumor-related immunological abnormalities, mutation landscape and pathway dysregulation, and clinical outcome. Further, we developed a 13-gene prognostic model for AML from DEG analysis in the two subtypes. A risk score was calculated for each patient then the overall group was stratified into high- and low-risk groups; the higher risk score correlated with short survival. The model was validated in both independent AML cohorts and pan-cancer cohorts, which demonstrated robustness and extended usage of the model. A nomogram was constructed that integrated risk score, FLT3-ITD, TP53, RUNX1 mutations, and age. This nomogram had the additional value of discriminating the sensitivity of several chemotherapeutic drugs and ferroptosis inducers in the two risk groups, which increased the translational value of this model as a potential tool in clinical management. Through integrated analysis of ferroptosis pattern and its related model, our work shed new light on the relationship between ferroptosis and AML, which may facilitate clinical application and therapeutics.